Magnetic reconnection at a thin current sheet separating two interlaced flux tubes at the Earth's magnetopause - Kacem,I; Jacquey,C; Génot,V; Lavraud,B; Vernisse,Y; Marchaudon,A; Le,Contel O; Breuillard,H; Phan,TD; Hasegawa,H; Oka,M; Trattner,KJ; et al. (Journal of Geophysical Research: Space Physics, 2018)
The occurrence of spatially and temporally variable reconnection at the Earth's magnetopause leads to the complex interaction of magnetic fields from the magnetosphere and magnetosheath. Flux transfer events (FTEs) constitute one such type of interaction. Their main characteristics are (1) an enhanced core magnetic field magnitude and (2) a bipolar magnetic field signature in the component normal to the magnetopause, reminiscent of a large-scale helicoidal flux tube magnetic configuration. However, other geometrical configurations which do not fit this classical picture have also been observed. Using high-resolution measurements from the Magnetospheric Multiscale mission, we investigate an event in the vicinity of the Earth's magnetopause on 7 November 2015. Despite signatures that, at first glance, appear consistent with a classic FTE, based on detailed geometrical and dynamical analyses as well as on topological signatures revealed by suprathermal electron properties, we demonstrate that this event is not consistent with a single, homogenous helicoidal structure. Our analysis rather suggests that it consists of the interaction of two separate sets of magnetic field lines with different connectivities. This complex three-dimensional interaction constructively conspires to produce signatures partially consistent with that of an FTE. We also show that, at the interface between the two sets of field lines, where the observed magnetic pileup occurs, a thin and strong current sheet forms with a large ion jet, which may be consistent with magnetic flux dissipation through magnetic reconnection in the interaction region.